Lakes: A 4D Book - Shores, Erika L. 1976- (North Mankato, Minnesota An imprint of Pebble, 2019)
Simple text describes how lakes form, the plants and animals in lakes, and how people use lakes. Download the Capstone 4D app to access a variety of bonus content.
Accelerated Reader AR
Keywords: Lakes -- Juvenile literature; Lake animals -- Juvenile literature; Lake ecology -- Juvenile literature